Low-Profile Dual-Band Reflector Antenna for High-Frequency Applications - Lu, Senlin; Qu, Shi-Wei (Sensors (Basel, Switzerland), 2023)
A high-gain low-profile reflector antenna with dual-band radiation ability is presented in this paper. The antenna achieves a relative 2 dB gain bandwidth of 10% around fl, and a relative 2 dB gain bandwidth of 20%, around fh, where fl and fh are the center operating frequencies of the frequency bands of 29.4~32.4 GHz and 142~174 GHz, respectively. To achieve the dual-band radiation ability, a composite dual-band feed with an fh/fl ratio of around 5 is proposed as the feed for the reflector antenna, which includes a higher-band circular waveguide and a lower-band coaxial horn. The metallic elliptical surface serves as the subreflector (SR) in the higher band, while the SR is the planar reflectarray in the lower band. Due to the design of the dual reflector, the dual-band reflector antenna features a low focal-to-diameter (F/D) ratio of approximately 0.2. According to the simulated results, the proposed reflector antenna achieves efficiencies of 59.0% and 42.9% at fl and fh, respectively. For verification purposes, a Ku/E-band scaled prototype is manufactured. The measured VSWRs, radiation patterns, and gains are in reasonable agreement with the simulated ones, proving the correctness of the proposed design method.